O RACIOCÍNIO DE PROPORCIONALIDADE SOB A LUZ DA RESOLUÇÃO DE PROBLEMAS COM ESTUDANTES DO 7° ANO DO ENSINO FUNDAMENTAL - Matulle, Luciano (2019)
These studies aimed contribute with the solution of one of the problems identified during the Basic Education, in the subject of Mathematic: The Proportionality Teaching. In this way, was considered how a guide question: with base on Theory of Conceptual Fields, which potentially are noticed in a teaching methodology based on Problems Resolution, on the development of proportionality? The investigation was featured as a practice research-action, seeking in parallel with the research; make an action aim the solution of a learning problem. The development occurred through participating observation and pedagogical intervention, in a class of seventh year of an Elementary school, in a public school in the countryside from the city of Pinhão - Pr. It was considered as a teaching methodology of the Problem Resolution, according to the conception to teach via Problem Resolution. In this conception, the problems are proposed to the students before is has been submitted formally the mathematic content. In agreement with the theory of the Conceptual Fields from Gerard Vergnaud, was possible identify the main difficulties presented for the students in the resolution of problems and point the ways and procedures to be followed for the teacher to the students learn about proportionality. The most valuable contribution of PR in relation to in the changing of attitudes of the students, in the engagement in the classroom, in the creation and diversification of the strategies of solution , in the thinking about solution problems and in the elaboration of the reasoning of proportionality.